JAPANESE ENTERPRISES ROLE ON SMES DEVELOPMENT IN INDONESIA: INSIDE TOBIKO EXPORT AND IMPORT - Muh. Yushar Mustafa; Fahrina Mustafa; Riad Mustafa; Rahmat Mustafa (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2018)
The behavior and the performance of firms, which are highlighted on small and medium-sized enterprise (SME) development, have been extensively discussed since few past decades among the scholars and researchers. Nonetheless, most of those studies only concentrate onto Western firms and less is known in South-East Asia firms, especially the firms located in Indonesia. Consistent with the lack of literature mentioned above, the most significant problem within the body of literature is there are also very little comprehensive findings of empirical research in examining the role of foreign enterprises which specialized in flying fish roe product, known as Tobiko or To Bio No Tamago in Japanese, on the development of Indonesian SMEs in general and the development of natives’ wealth and knowledge in particular. To this knowledge, this study thus aims to expound the role of Kanetoku Corporation and Kanematsu Corporation (formerly known as Kanematsu Gosho Ltd.) – as the representative of the foreign firms – on the development of Indonesian SMEs that are originated from South Sulawesi province, especially from Makassar, Takalar, and Mamuju region. Through the application of resource-based view (RBV) as the grounded theory and the emphasis on the underpinning concept of innovation and knowledge-transfer, this study is strongly expected come up with the result that innovation and knowledge transfer provided by Japanese firms intentionally or unintentionally have become the vital factors on the development of South Sulawesi SMEs that can be seen for example within (1) the successful internationalization of South Sulawesi SMEs and amusingly (2) the remarkable discovery of a new habitat of flying fish outside the South Sulawesi province by the South Sulawesi SMEs during the collaboration between Japanese firms.